PELATIHAN DAN PENDAMPINGAN PEMBUATAN VIDEO PEMBELAJARAN DAN PROMOSI DI SLB NEGERI 2 BANTUL - Syah, Firdiyan; Tentua, Meilani Nonsi; Saputra, Nurirwan (Pusat Riset dan Inovasi Nasional, 2022)
The Covid-19 pandemic has forced the government to enforce a physical distancing policy which is the basis for implementing learning from home. This is also something that must be applied to students at SLB Negeri 2 Bantul. The use of information technology that applies suddenly, not infrequently, makes educators and students surprised and limping in its implementation. However, the learning process must continue so that teachers at SLB Negeri 2 Bantul are challenged to create a learning media that students with special needs can understand. The limited knowledge of teachers at SLB Negeri 2 Bantul in making learning media causes the need for training and mentoring of learning media. One of the technological developments that we can use for making learning media is an application for video editing. This application can help to make videos to improve the quality and effectiveness of learning. Application users are expected to support the activities of SLB Negeri 2 Bantul to participate in competitions and promotions as routine activities that must be done every year. The two needs of these teachers are what make them collaborate to implement training programs based on the required classes. The implementation uses the Classical method and Practices using video recording applications and equipment. Community service will be carried out at SLB Negeri 2 Bantul to support improving skills in using software from basic to advanced levels. The result of this training is that the participants can make their own video creations so that they are eligible to be included in competitions and make video advertisements more professional.